Appropriate Conservation Machinery for Mungbean Cultivation in the Southern Region of Bangladesh - M., A. Hossain; M., A. Mottalib; M., I. Hossain; M., N. Amin; M., M. Alam; C., K. Saha (Journal of Precision Agriculture, 2018)
The study was conducted at Mundopasha, Wazirpur, Barisal during Rabi season of 2017 for testing, adoption and popularization of different conservation machinery (CA) such as zero till planter (ZT), strip till planter (ST), bed planter (BP) and power tiller operated seeder (PTOS) along with conventional tilling and of sowing method for planting of mungbean (BARI Mung-6). The soil type was loamy-sand with bulk density 1.41 g/cc. The effective field capacities of ZT, ST, BP, PTOS and power tiller were found to be 0.104, 0.109, 0.084, 0.109, and 0.074 ha/h, respectively. The field efficiency of ZT, ST, BP, PTOS and power tiller were estimated as 74.68, 76.47, 75.84, 78.16 and 71.52%, respectively. Significantly the highest mungbean grain yields were found from ZT and ST planted plots than those of other plots. Significantly the lowest grain yield was obtained from conventional tillage and broadcasting method. The highest benefit cost ratio (BCR) was obtained from ST planted (2.60) and zero till planted (2.40) mungbean followed by PTOS (2.20), conventional tillage cum broadcasting (1.88) and bed planting (1.82) methods. The lowest BCR was found from traditional tillage and manual line sowing method (1.61) of mungbean. CA planting system saved about 50% planting cost and reduced about 76% carbon dioxide emission. Based on the fuel consumption, grain yield and BCR, ZT planter and the strip till planter may be recommended in Barisal region for cultivation of mungbean.
Keywords: Conservation agriculture; zero tillage; minimum tillage; strip tillage; bed planting; southern region